Iloprost Duration for Digital Ulcers in Systemic Sclerosis: French Retrospective Study at Two Centers and Literature Review - Jamart, Céline; Levesque, Hervé; Thietart, Sara; Fain, Olivier; Rivière, Sébastien; Benhamou, Ygal; Mekinian, Arsène (Frontiers in Medicine, 2022)
Ischemic digital ulcers are frequent and severe complications of systemic sclerosis. The aim of this study was to determine whether prolonging intravenous prostanoids infusion beyond 5 days increases the rate of healing of active DUs. This is an observational longitudinal retrospective multicenter study. Forty-one patients, with mean age of 47±15 years at diagnosis and 32 females have been included. Systemic sclerosis was diffuse in 10 cases and 13 had an interstitial lung disease. A total of 243 iloprost infusions for DUs were performed: 140 infusions for ≤5 days, and 103 infusions for >5 days Patients with active DUs who received >5 days of iloprost had higher Rodnan scale at the time of iloprost infusion, more interstitial lung diseases, more anti-topoisomerase I antibodies positivity, and more previous cyclophosphamide therapy. While the number of active DUs before iloprost infusion was not significantly different among those who received ≤5 days and >5 days of iloprost, the time to healing after iloprost infusion significantly decreased in SSc patients who received >5 days iloprost infusion: 48 versus 91days. The proportion of SSc patients with healed DUs tended to increase in patients with >5 days iloprost infusion. The number of patients with complete ulcer healing at day 90 was significantly increased in >5 days of iloprost group. In addition, the time to healing was not significantly associated with the use of calcium channel blockers, endothelin receptor antagonists or a combination of PDE-5 inhibitors. Prolonging duration of iloprost may improve healing rate and time of SSc-related DUs.